A General Model to Explain Repeated Turnovers of Sex Determination in the Salicaceae. (7th October 2020) - Yang, Wenlu; Wang, Deyan; Li, Yiling; Zhang, Zhiyang; Tong, Shaofei; Li, Mengmeng; Zhang, Xu; Zhang, Lei; Ren, Liwen; Ma, Xinzhi; Zhou, Ran; Sanderson, Brian J; et al.
Abstract: Dioecy, the presence of separate sexes on distinct individuals, has evolved repeatedly in multiple plant lineages. However, the specific mechanisms by which sex systems evolve and their commonalities among plant species remain poorly understood. With both XY and ZW sex systems, the family Salicaceae provides a system to uncover the evolutionary forces driving sex chromosome turnovers. In this study, we performed a genome-wide association study to characterize sex determination in two Populus species, P. euphratica and P. alba . Our results reveal an XY system of sex determination on chromosome 14 of P. euphratica, and a ZW system on chromosome 19 of P. alba . We further assembled the corresponding sex-determination regions, and found that their sex chromosome turnovers may be driven by the repeated translocations of a Helitron -like transposon. During the translocation, this factor may have captured partial or intact sequences that are orthologous to a type-A cytokinin response regulator gene. Based on results from this and other recently published studies, we hypothesize that this gene may act as a master regulator of sex determination for the entire family. We propose a general model to explain how the XY and ZW sex systems in this family can be determined by the same RR gene. Our study provides new insights into the diversification of incipient sex chromosomes in flowering plants by showing how transposition and rearrangement of a single gene can control sex in both XY and ZW systems.